2020
DOI: 10.6018/eglobal.381641
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, habilidades de comunicación y autoeficacia en los profesionales de urgencias y cuidados críticos

Abstract: Objetivo: Analizar el nivel y la relación entre habilidades de comunicación, autoeficacia percibida y síndrome de Burnout en profesionales de la salud del servicio de urgencias hospitalario y unidad de cuidados críticos de un hospital comarcal. Método: Se plantea un estudio observacional y transversal en una muestra de 90 profesionales sanitarios de un Hospital Comarcal, 19 médicos (21,1%), 47 enfermeros (52,2%), 24 auxiliares de enfermería (26,7%). Se han usado la Escala sobre Habilidades de Comunicación en P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
7
Order By: Relevance
“…In this sense, Castaño et al [58] conducted a study with doctors of EDs, confirming that self-efficacy is a key aspect in emotional control. These observations have also been confirmed by others [59,60]. The results from our work show a high rate of self-efficacy (29 out of 40).…”
Section: Stress and Self-efficacy In The Studied Ed Professionalssupporting
confidence: 92%
“…In this sense, Castaño et al [58] conducted a study with doctors of EDs, confirming that self-efficacy is a key aspect in emotional control. These observations have also been confirmed by others [59,60]. The results from our work show a high rate of self-efficacy (29 out of 40).…”
Section: Stress and Self-efficacy In The Studied Ed Professionalssupporting
confidence: 92%
“…A qualitative systematic review found that nurses working on the front lines during the COVID-19 pandemic experienced psychological, social, and emotional distress [ 46 ], and during this time, the health professional’s stress increased in Spain [ 47 ]. It has been demonstrated that adequate training on communication skills could have a direct impact on the mental health of workers and especially against burnout syndrome [ 17 , 20 ]. It has also been observed that the impact of the communication skills of emergency professionals is correlated with the satisfaction perceived by the patients and family members [ 48 ] and that communication skills improve the self-efficiency in professional practice perceived by the nursing professionals themselves [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on health professionals and communication skills can be equated to investing in better patient care [ 16 ]. It has also been observed that good communication skills are fundamental for preventing the burnout syndrome found in health professionals [ 17 , 18 , 19 , 20 ]. Furthermore, communication failures are the leading cause of inadvertent patient harm [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…W zakresie komunikacji informatywnej kobiety cechowały się wyższą średnią, podobnie jak mężczyźni (N = 22) w za kresie asertywności, ale bez istotności statystycznej [34]. Zaś w badaniu personelu medycznego nie stwierdzono istotnych statystycznie różnic pomiędzy żadnym z wymiarów, przy czym kobiety (N = 65) uzyskały wyższą średnią w zakre sie empatii, a w pozostałych trzech wymiarach mężczyźni (N = 25) charakteryzowali się wyższą średnią, przy czym badaniem objętych było jedynie 19 lekarzy [35]. Inne badania pokazują istotne statystycznie różnie w zakresie komunikacji informatywnej i empatii wśród lekarzy i pielęgniarek, przy czym pielęgniarki osiągały istotnie wyższe wyniki w zakresie obu podskal.…”
Section: Dyskusjaunclassified